Grid indentation analysis of composite microstructure and mechanics: principles and validation - Constantinides, Georgios; Ravichandran, K. S R; Ulm, Franz Josef (My University, 2006)
Several composites comprise material phases that cannot be recapitulated ex situ, including calcium silicate hydrates in cementitous materials, hydroxyapatite in bone, and clay agglomerates in geomaterials. This requirement for in situ synthesis and characterization of chemically complex phases obviates conventional mechanical testing of large specimens representative of these material components. Current advances in experimental micro and nanomechanics have afforded new opportunities to explore and understand the effect of thermochemical environments on the microstructural and mechanical characteristics of naturally occurring material composites. Here, we propose a straightforward application of instrumented indentation to extract the in situ elastic properties of individual components and to image the connectivity among these phases in composites. This approach relies on a large array of nano to microscale contact experiments and the statistical analysis of the resulting data. Provided that the maximum indentation depth is chosen carefully, this method has the potential of extracting elastic properties of the indented phase which are minimally affected by the surrounding medium. An estimate of the limiting indentation depth is provided by asssuming a layered, thin film geometry. The proposed methodology is tested on a "model" composite material, a titanium-titanium monoboride (Ti-TiB) of various volumetric proportions. The elastic properties, volume fractions, and morphological arrangement of the two phases are recovered. These results demonstrate the information required for any micromechanical model that would predict composition-based mechanical performance of a given composite material.
Keywords: Hydroxyapatite; Mathematical models; Nanostructured materials; Statistical methods